PENINGKATAN PENDAPATAN KELUARGA PADA MASA PANDEMI COVID-19 DI KELURAHAN MANGUNHARJO KECAMATAN TEMBALANG KOTA SEMARANG - Tri Endang Yani; Totok Wibisono; Anantyo Roestanto (LPPM Institut Desain dan Bisnis Bali, 2022)
At this time the whole world is being hit by the COVID-19 pandemic which has a very bad impact on all aspects of human life. As a result of the Covid-19 pandemic in the economic field, the economy is paralyzed, layoffs occur, companies enforce work from home (WFH) for their employees, small and micro businesses are out of business. The implementation of WFH and the number of stalled businesses have caused many residents to have free time at home. As a result, it can be ascertained that the income of many people is reduced. This condition is felt by the people in the Mangunharjo sub-district, Tembalang sub-district, Semarang City. With this background in mind, the community service team made efforts to increase family income. The purpose of Community Service is to provide knowledge about entrepreneurship and training to make products for housewives. The method of implementing community service activities is the lecture and discussion method as well as training. Evaluation is done by distributing questionnaires. The results achieved after community service are positive changes for mothers in terms of knowledge and understanding of entrepreneurship, an increase in enthusiasm for entrepreneurship and being able to create creative ideas to run entrepreneurship. The training provided can increase the skills of mothers in making laundry soap products that can be sold so that they are expected to increase family income.